Surgical delivery of drug releasing poly(lactic-co-glycolic acid)/poly(ethylene glycol) paste with in vivo effects against glioblastoma - Smith, Stuart J.; Rahman, Cheryl V.; Clarke, P.A.; Ritchie, A.A.; Gould, Toby W.A.; Ward, Jennifer H.; Shakesheff, Kevin M.; Grundy, Richard G.; Rahman, Ruman (Royal College of Surgeons of England, 2014)
Introduction: The median survival of patients with glioblastoma multiforme (astrocytoma grade 4) remains less than 18 months despite radical surgery, radiotherapy and systemic chemotherapy. Surgical implantation of chemotherapy eluting wafers into the resection cavity has been shown to improve length of survival but the current licensed therapy has several draw- backs. This paper investigates in vivo efficacy of a novel drug eluting paste in glioblastoma. Methods: Poly(lactic-co-glycolic acid)/poly(ethylene glycol) (PLGA/PEG) self-sintering paste was loaded with the chemothera- peutic agent etoposide and delivered surgically into partially resected tumours in a flank murine glioblastoma xenograft model. Results: Surgical delivery of the paste was successful and practical, with no toxicity or surgical morbidity to the animals. The paste was retained in the tumour cavity, and preliminary results suggest a useful antitumour and antiangiogenic effect, particularly at higher doses. Bioluminescent imaging was not affected significantly by the presence of the paste in the tumour. Conclusions: Chemotherapy loaded PLGA/PEG paste seems to be a promising technology capable of delivering active drugs into partially resected tumours. The preliminary results of this study suggest efficacy with no toxicity and will lead to larger scale efficacy studies in orthotopic glioblastoma models.